Formulações e métodos de solução para o problema de coleta e entrega com janelas de tempo, frota heterogênea e múltiplos produtos - Gasque, Diógenes Henrique Frazzato (2019)
Logistics efficiency is critical to the business success of most organizations. Inherent in the logistics process, vehicle routing plays an important role to ensure lower costs and customer satisfaction. The vehicle routing problem with pickup and delivery arises in several real-word contexts in both urban and rural environments, where products are collected in certain locations and transported to the respective delivery recipients. Usually these pickup and delivery operations should consider more complex decisions, such as customer time windows, heterogeneity of the fleet, and quantities to be transported of the various existing products. We address the pickup and delivery vehicle routing problem with time windows, with practical constraints of heterogeneous fleet, multiple products and split load. We proposed models and solution methods for the problem in question. We extended a three-index model based on the classical formulation containing all practical constraints. We adapted a two-index model containing heterogeneous fleet and multiple products. Computational experiments using examples from literature showed that the models and methods proposed had acceptable results. We proposed a metaheuristic for the classical case and its variants. To facilitate the use of the proposed approaches for the support of decision-making, we developed a computational tool with web interface, and show the results of this tool.